Implikasi Pencatatan Sipil Akibat Perbedaan Asas Kewarganegaraan yang Dianut Antar Negara - Awalin, Hanif Fil; Rasendriya, Bariq Raditya; Mahira, Andi Humaira; Pramudita, Salmanita Shalsabella; Kusmaputri, Reta Indah; Ardian, Muhammad; Sakti, Muthia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Considering the importance of these events, in order to create an orderly and orderly society and to ensure legal certainty, a regulation is needed that regulates them. The regulations in question are regulations in the field of civil registration implemented by the civil registration institution, namely the Civil Registry Office. In this research, the author used normative research. This legal research is often referred to as doctrinal legal research which conceptualizes writing in statutory regulations or laws which are used as a benchmark for people's lives. The problem approach used is a statutory approach and a conceptual approach. The results of the research show that the Civil Registry (Burgerlijke Stand) is an institution established by the authorities which aims to prove as completely as possible and therefore provide maximum certainty about all events that are important for a person's civil status regarding birth, confession, marriage, divorce and death. . Differences in civil registration resulting from different citizenship principles in mixed marriages can affect the rights and obligations of citizens. These differences reflect the complexity in the legal and administrative systems of different countries, and emphasize the importance of having accurate and complete civil registration to ensure fair and equal rights and obligations of citizens.